2020
DOI: 10.3389/fnsys.2020.581830
|View full text |Cite
|
Sign up to set email alerts
|

The Lateral Preoptic Area and Its Projection to the VTA Regulate VTA Activity and Drive Complex Reward Behaviors

Abstract: The ventral tegmental area (VTA) underlies motivation and reinforcement of natural rewards. The lateral preoptic area (LPO) is an anterior hypothalamic brain region that sends direct projections to the VTA and to other brain structures known to regulate VTA activity. Here, we investigated the functional connection between the LPO and subpopulations of VTA neurons and explored the reinforcing and valence qualities of the LPO in rats. We found that the LPO and the LPO→VTA pathway inhibit the activity of VTA GABA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…However, our prior work found no relationship between LPO firing rates and locomotor activity (Barker et al, 2015). Moreover, one recent study failed to find an increase in general locomotor activity in a context associated with operant responding (Gordon-Fennell et al, 2020), and additional work has suggested that this locomotor activity may reflect fixed action patterns (Reichard et al, 2019).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…However, our prior work found no relationship between LPO firing rates and locomotor activity (Barker et al, 2015). Moreover, one recent study failed to find an increase in general locomotor activity in a context associated with operant responding (Gordon-Fennell et al, 2020), and additional work has suggested that this locomotor activity may reflect fixed action patterns (Reichard et al, 2019).…”
Section: Discussionmentioning
confidence: 69%
“…It would therefore be of great interest for future studies to examine whether these responsive ensembles comprise a specific cell-type or project to a particular structure; projections to the LHb (Barker et al, 2017), VTA (Gordon-Fennell et al, 2020;Gordon-Fennell et al, 2019), or RMTG (Yetnikoff et al, 2015) are all compelling targets. Additionally, with the recent finding that the LPO may play an important role in drug relapse and decision making during relapse (Gordon-Fennell et al, 2020), more work is needed to determine the roles of specific LPO neuronal subtypes in supporting drug-seeking behavior. A better understanding of these processes could aid in the development of therapies to sustain drug abstinence in the face of repeated conflict.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The LPO participates in a wide variety of behaviours from locomotion (Reichard et al, 2019; Shreve & Uretsky, 1991; Subramanian et al, 2018; Zahm et al, 2014) and thirst (Saad et al, 1996), to reward‐seeking (Gordon‐Fennell et al, 2020) and aversive processing (Barker et al, 2017; Briski & Gillen, 2001). Most notably, the LPO supports strong intracranial self‐stimulation (Bushnik et al, 2000; Gallistel et al, 1985; Nakahara et al, 1999), and excitotoxic lesions of the LPO attenuate the rewarding efficacy of medial forebrain bundle self‐stimulation (Arvanitogiannis et al, 1996).…”
Section: Introductionmentioning
confidence: 99%